The Canadian context for evidence-based conservation and environmental management. Issue 1 (December 2016) - Cooke, Steven; Rice, Jake; Prior, Kent; Bloom, Robin; Jensen, Olaf; Browne, David; Donaldson, Lisa; Bennett, Joseph; Vermaire, Jesse; Auld, Graeme
Abstract Canada has strong institutional capacity for science-based decision-making related to natural resource conservation and environmental management. Yet, the concept of using systematic reviews (conducted in accordance with established guidelines) to support evidence-based conservation and environmental management in Canada is in its infancy. Here we discuss the Canadian context for implementing more rigorous evidence-based approaches using systematic reviews. Of particular relevance to Canada is its vast size, broad diversity of ecosystems and heavy economic reliance on natural resources that vary widely in the type and scale of their environmental effects. These factors result in a wide variety of environmental monitoring needs over an extensive area that pose challenges to the scientific community charged with overseeing wise use of the environment. In addition, there are diverse and engaged user groups (e.g., hunters, trappers, fishers, bird watchers, foresters) and indigenous peoples that have constitutional rights to their natural resources. Traditional environmental knowledge is a complementary source of evidence in the Canadian environmental impact assessment process and therefore must be a part of evidence synthesis. Systematic reviews are not intended to replace local field studies, but rather have the opportunity to draw upon a broader suite of evidence that can be interfaced with local perspectives. The existing institutional structures in Canada could easily incorporate systematic reviews into their science advice and decision-making frameworks but to date, there are few examples of where this has occurred. Drawing on the expertise of a growing global collaboration for environmental evidence synthesis, Canadian institutions (federal, provincial and NGO) are poised to more broadly incorporate systematic reviews once their benefits are fully realized and the capacity to undertake such systematic reviews is fully developed. Systematic reviews offer a consolidated view of the available scientific literature on a given question. The results may offer significant value when working with stakeholders and decision makers contributing other sources of information to the question. For example, mechanisms to capture and integrate scientific knowledge with stakeholder and traditional knowledge may benefit from the scientific sources being filtered, interpreted and summarized for discussion. In other cases, where timeframes for decision making preclude formal systematic reviews, opportunities for more rapid evidence synthesis methods will be needed before the concept will be fully embraced.